Gender-based in vivo comparison of culprit plaque characteristics and plaque microstructures using optical coherence tomography in acute coronary syndrome - Krishna Prasad; Sreeniavs Reddy S; Jaspreet Kaur; Raghavendra Rao k; Suraj Kumar; Vikas Kadiyala; Jeet Ram Kashyap; Garima Panwar (Journal of Cardiovascular and Thoracic Research, 2021)
Introduction: Women perform worse after acute coronary syndrome (ACS) than men. The reason for these differences is unclear. The aim was to ascertain gender differences in the culprit plaque characteristics in ACS. Methods:Patients with ACS undergoing percutaneous coronary intervention for the culprit vessel underwent optical coherence tomography (OCT) imaging. Culprit plaque was identified as lipid rich,fibrous, and calcific plaque. Mechanisms underlying ACS are classified as plaque rupture, erosion,or calcified nodule. A lipid rich plaque along with thin-cap fibroatheroma (TCFA) was a vulnerable plaque. Plaque microstructures including cholesterol crystals, macrophages, and microvessels were noted. Results: A total of 52 patients were enrolled (men=29 and women=23). Baseline demographic features were similar in both the groups except men largely were current smokers (P<0.001). Plaque morphology,men vs. women: lipid rich 88.0% vs. 90.5%; fibrous 4% vs 0%; calcific 8.0% vs. 9.5% (P = 0.64). Of the ACS mechanisms in males versus females; plaque rupture (76.9 % vs. 50 %), plaque erosion (15.4 % vs.40 %) and calcified nodule (7.7 % vs. 10 %) was noted (P = 0.139). Fibrous cap thickness was (50.19 ±11.17 vs. 49.00 ± 10.71 mm, P = 0.71) and thin-cap fibroatheroma (96.2% vs. 95.0%, P = 1.0) in men and women respectively. Likewise no significant difference in presence of macrophages (42.3 % vs. 30%, P = 0.76), microvessels (73.1% vs. 60 %, P = 0.52) and cholesterol crystals (92.3% vs. 80%, P = 0.38). Conclusion: No significant gender-based in-vivo differences could be discerned in ACS patients’ culprit plaques morphology, characteristics, and underlying mechanisms.